Masker SENGAT API (Senyum Semangat Aromaterapi) Solusi Atasi Kantuk Saat Berkendara - Yesita, Nita; Anggraini, Feni Dwi; Seviana, Foni; Fadhilah, Khairunnisa; Dwitama, Putri Aprilia (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
âMasker Sengat Apiâ was mask of aromatherapy which served as an effective solution to overcome drowsiness for riders. It was well known that one factor contributed to the high number of traffic accidents in Indonesia are caused by human neglience that is the condition of the rider was tired and sleepy that endangered the lives of riders and others. This mask inserted with aromatherapy gel made from natural ingredients with a fresh scent and had stimulant effect (orange, lemon, peppermint, and greentea) but did not have harmful side effect. This product was easy to use and fun for riders, especially with its unique shape and designed as well as affordable price. Stages of production âMasker Sengat Apiâ included pre production survey of availability of raw materials and the manufactured of masks and packaging designed, followed by production stage. This product has been publicized through speeched with others or writing and marketed âmobileâ in Bandung and Jatinangor 1072 pieces of mask and 468 pieces aromatherapy gell refill pack. Based on the activity of PKM-K can be concluded that the students were able to be independent and aved an entrepreneurial spirit by selling the innovative products âMasker Sengat Apiâ that were able to sensitize the public to always overcome drowsiness in driving as well as being a practical choice in selecting a mask with all its benefits. Keywords : PKM-K, Mask, Aromatherapy, Sengat Api, Drowsiness